What Can Ukraine Learn from Aufbau Ost? - Ulrich Blum (Intereconomics, 2023)
This article uses Aufbau Ost (or reconstruction of the East) of the new German states as a structural model to estimate the possible costs of an Aufbau Ost 2.0 of Ukraine while taking institutional differences into account. Based on three approaches, the model is validated for the new German states - namely capital coefficients, actual investment flows and actual public transfers - and applied to Ukraine. Key indicators for Germany from 2021 are used as a basis. The economic goal for Ukraine set in this article is to reach Poland's present level of prosperity in 15 years, which implies a growth rate of 9% per year. This will require a total of US 8.5 trillion over 15 years, which can, however, be financed to a considerable extent by endogenous, investment-driven economic growth if the institutional framework conditions are designed in a market-economy way, especially the taxation system. Transfers and capital imports must close a current account deficit of about US 200 billion per year.
Keywords: F1; O4; P5; 330; consequences of war; economic reconstruction; Ukraine; Kriegsfolgen; Wirtschaftlicher Wiederaufbau; Ukraine